Advances in business and management forecasting - Lawrence, Kenneth D.; Klimberg, Ronald K. (Advances in business and management forecasting, 2014)
The objective of this research annual is to present state-of-the-art studies in the application of forecasting methodologies to such areas as sales, marketing and strategic decision making. It is the hope and direction of this research annual to become an applications and practitioner oriented publication.